Opportunities and challenges of implementing an urban primary healthcare delivery model: Programmatic lessons from Aalo Clinic, Bangladesh - Khadija Islam Tisha; Mohammad Wahid Ahmed; A M Rumayan Hasan; Orin Akter; Md. Golam Rabbani; Chandrasegarar Soloman; Margub Aref Jahangir; Maya Vandenent; Shehrin Shaila Mahmood (PLoS ONE, 2026)
Background Rapid urbanization in Bangladesh has strained the healthcare system, leaving urbanites underserved in primary healthcare (PHC). To address this gap, a UNICEF-supported Government of Bangladesh initiative introduced the Aalo Clinic model to expand access to affordable PHC. This study explored implementation challenges and opportunities of the Aalo Clinic model from a programmatic perspective for strengthening urban PHC delivery. Methods The opportunities and challenges of implementation were explored through qualitative research conducted between June 2022 and May 2023 in six Aalo Clinic intervention areas across four city corporations in Dhaka, Bangladesh. Twenty-four in-depth interviews with service providers and eighteen key informant interviews with clinic-in-charges, community leaders, scheme operators, and policymakers were conducted, along with periodic observations at clinics. A thematic analysis was performed to analyze the data. Results Three core themes evolved from the analysis – technical, administrative, and financial opportunities and challenges. Aalo Clinic’s integrated digitalized health platform reported to streamline operations through medical documentation and real-time monitoring. Initiatives like prescription audits and client feedback systems reported to promote rational prescribing and delivering quality care. However, key challenges included limited choice of medicine, interrupted internet connection, high patient flow, and longer waiting times. Despite challenges policymakers mentioned Aalo Clinic’s potential to integrate into the national health system, highlighting the need for coordinated efforts to overcome obstacles. Financial sustainability, however, hinges on the model’s integration into the government system and the provision of public funding to support its implementation. Conclusion The study underscores the importance of addressing implementation challenges while capitalizing on opportunities to scale up the Aalo Clinic model. Recommendations include implementing structured monitoring, ensuring need-based medicine supply, fostering collaboration with the government for referrals, and facilitating cross-learning among urban PHC facilities. By addressing implementation challenges and strengthening multisectoral collaboration, the Aalo Clinic model shows potential to contribute to improved access to quality PHC in urban settings, in line with the broader vision of health for all.